The Political Economy of Services Trade Agreements - Matteo Fiorini; Mathilde Lebrand (Center for Economic Studies and ifo Institute (CESifo), 2016)
Why do governments sign services trade agreements? This paper focuses on the role of international agreements in the context of trade in services when services are used as intermediate inputs in downstream industries. Compared to goods, services inputs are mostly non-tradable and complementary to other factors of production. We build a theoretical trade policy framework in which firms use foreign investment to contest foreign markets in services sectors and governments can restrict the entry of multinationals. Commitment helps governments to avoid political pressures that would result in protectionist measures leading downstream industries to inefficiently reduce their production. First we show that the role of services as complementary inputs is central to explain governments' commitment to services trade liberalization. Second we provide new results on the influence of lobbying by both national firms and foreign multinationals on trade policies and the gains from commitment. Finally we discuss how the bargaining power of the government, the size of national services sectors and the difference in valuation between national and foreign contributions affect the willingness of the government to sign a services trade agreement.
Keywords: D43; F13; F21; L80; 330; trade in services; trade agreements; FDI; lobbying